2022
DOI: 10.3748/wjg.v28.i35.5111
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs as additional mediators of epigenetic regulation in nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) has emerged as the most common cause of chronic liver disorder worldwide. It represents a spectrum that includes a continuum of different clinical entities ranging from simple steatosis to nonalcoholic steatohepatitis, which can evolve to cirrhosis and in some cases to hepatocellular carcinoma, ultimately leading to liver failure. The pathogenesis of NAFLD and the mechanisms underlying its progression to more pathological stages are not completely understood. Besides ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 159 publications
0
2
0
Order By: Relevance
“…Among them, miR-34a, miR-122 and miR-192 are the best candidates as biomarkers for NALFD diagnosis and staging, and may serve as therapeutic targets for NAFLD. [68][69][70][71][72] In a meta-analysis study, miR-34a showed the best diagnostic accuracy for discriminating NASH from NAFL. 72 In mice with miR-34a deficiency or overexpression in hepatocytes, or treated with miR-34a inhibitor, miR-34a has been demonstrated to promote NASH induced by a diet high in fat, cholesterol and fructose (HFCF).…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Among them, miR-34a, miR-122 and miR-192 are the best candidates as biomarkers for NALFD diagnosis and staging, and may serve as therapeutic targets for NAFLD. [68][69][70][71][72] In a meta-analysis study, miR-34a showed the best diagnostic accuracy for discriminating NASH from NAFL. 72 In mice with miR-34a deficiency or overexpression in hepatocytes, or treated with miR-34a inhibitor, miR-34a has been demonstrated to promote NASH induced by a diet high in fat, cholesterol and fructose (HFCF).…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…As previously highlighted, peroxisome proliferator-activated receptors (PPARs) regulate lipid homeostasis and have been proposed as important regulators in the development of NAFLD and its various stages. Furthermore, their cross-regulation with ncRNAs has emerged as an additional layer of complexity in the regulatory mechanisms of several diseases, including NAFLD [ 85 , 86 , 87 ]. Thus, expanding our knowledge of the ncRNAs/PPARγ regulatory axis may help us better understand how epigenetic mechanisms contribute to the physiopathology of NAFLD and advance the process of developing potential ncRNAs/PPARγ-based therapeutics for this condition.…”
Section: The Role Of Epigenetic Mechanisms In Regulating Pparγ Regula...mentioning
confidence: 99%